MEDIA KOMIK DIGITAL BERBASIS NILAI KARAKTER DALAM MUATAN PELAJARAN IPS TEMA “PAHLAWANKU” KELAS IV SEKOLAH DASAR - Neng Fitri Andriani; Arifin Maksum; Prayuningtyas Angger Wardhani (JURNAL PENDIDIKAN DASAR, 2022)
This development research aims to: (1) develop digital comic media products based on character values as social studies learning media in the fourth grade of elementary school, and         (2) knowing feasible the digital comic media based on character values that were develop. The research was carried out in class IV SDN Makasar 06 East Jakarta from October 2020 to July 2021. The research method used was the research and development (RD) method with the ADDIE development model. Data collection techniques using observation, interviews, and questionnaires. The development of research involving multiple respondents, one expert lecturer's material, one media expert lecturer, one lecturer linguist, and learners in grade IV SDN 06 Makasar East Jakarta, amounting to 12 to assess the feasibility of digital comics media products developed. The results showed that digital comic media based on character values was considered very good. This can be seen based on the average value of the material, media, and language expert validation tests of 93.44% in the very good category, and the student trial score of 96.69% in the very good category. Based on the explanation above, this character value-based digital comic media is included in the very good category, so it is feasible to be used as a learning medium in social studies subject matter in grade IV SD.